Søren Dietz, Fanis Mavridis, Žarko Tankosić and Turan Takaoğlu (eds). Communities in transition. The circum-Aegean area during the 5th and 4th millennia BC - Dickinson, Oliver (Journal of Greek Archaeology, 2019)
This is a massive book, deriving from a multi-paper conference held in Athens, and really there is too much material for a single hardback volume, which seems to have affected the quality of the binding (on the reviewer’s copy the front cover split from the spine at the top quite quickly). The conference was intended to focus on the social changes that occurred during the development from Neolithic to Early Bronze Age in the later 5th and 4th millennia BC, the period widely defined as Final Neolithic in Aegean terminology, in the ‘circum-Aegean area’. After an explanatory preface by the editors, an Introduction contains the editors’ summary presentation of their view of the content and value of the papers, arranged first by significant themes, then by survey and site reports within the regions between which the papers have been distributed.